Validation of international classification of diseases, tenth revision, clinical modification diagnosis codes for heart failure subtypes. Issue 9 (29th June 2022) - Pocobelli, Gaia; Ichikawa, Laura; Yu, Onchee; Green, Beverly B.; Meyers, Kelly; Gray, Regan; Shea, Mary; Chubak, Jessica
Abstract: Purpose: To estimate the positive predictive value (PPV) of International Classification of Diseases, Tenth Revision, Clinical Modification (ICD‐10‐CM) diagnosis codes for identifying HF subtypes. Methods: We validated ICD‐10‐CM HF diagnosis codes among Kaiser Permanente Washington enrollees who were ≥18 years of age and had an ICD‐10‐CM HF diagnosis code during 2017–2018 and a procedure code for an echocardiogram in the 12 months before through 6 months after the HF code. Left ventricular ejection fraction (LVEF) ascertained from medical chart review was used as the gold standard for classifying patients as having reduced ejection fraction (rEF), mid‐range ejection fraction (mEF), or preserved ejection fraction (pEF). Results: Among 6194 eligible patients, we randomly sampled 1000 for medical chart review. A total of 974 patients had LVEF information in their chart. The ICD‐10‐CM HF code group with the highest PPV for rEF was I50.20‐I50.23, "Systolic (congestive) heart failure, " PPV = 41.4% (95% CI, 34.5–48.7%); and the highest PPV for mEF or rEF was also I50.20‐I50.23, PPV = 70.2% (95% CI, 63.1–76.4%). The highest PPV for pEF was the I50.30‐I50.33 group, "Diastolic (congestive) heart failure, " PPV = 92.0% (95% CI, 88.1–94.7%); and the highest PPV for mEF or pEF was also I50.30‐I50.33, PPV = 97.7% (95% CI, 95.1–99.0%). Conclusions: If the accuracy measure of greatest interest is PPV, our results suggest that ICD‐10‐CM HF codes alone may not be adequate for identifying patients with rEF but may be adequate for identifying patients with pEF. HF coding practices may vary across settings, which may impact generalizability of our findings.